COOPERATION OR COMPETITION DURING THE PANDEMIC OF COVID-19? A CRITICAL ANALYSIS OF REALPOLITIC WORLDVIEW (Security Dialogues, 2023)
The Covid-19 virus emerged firstly in the Wuhan city of China in late 2019 andquickly spread to the rest of the world. A few months later the states and World HealthOrganization securitized the virus, then it has become a severely full-scale health crisis atthe global level. The Covid-19 pandemic has threatened all humanity irrespective of race,nation, religion, and ethnicity except socio-economic class, and has brought widespreadinsecurity, risk, and uncertainty around the world. Moreover, the pandemic has been a testfor cooperative relations among states in the international system. The Covid-19 pandemicis a global problem but the response against the virus has been mostly national during thepandemic. In this context, the paper aims to evaluate the pandemic conditions critically andmakes a comparison between the pre-pandemic era and the pandemic era of world politics.The paper concludes that although global problems ask for global solutions, concepts suchas egocentrism, nationalism, and national security have increased their importance in theinternational system instead of cooperation and global solidarity during the pandemic.
Keywords: Realpolitik, Cooperation, Competition, Pandemic, Covid-19